Blood Catalase Activities, Catalase Gene Polymorphisms and Acatalasemia Mutations in Hungarian Patients with Diabetes Mellitus - Góth L; Nagy T; Paragh G; Káplár M (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2016)
Introduction: Catalase decomposes hydrogen peroxide into oxygen and water. Its low concentration could be involved in signaling while its high concentration is toxic. Aim: This short review discusses the association of blood catalase and diabetes mellitus in Hungarian diabetic patients. Results: Several cohort studies showed decreased blood catalase activity in type 2 diabetes and in gestational diabetes.  Among the catalase gene polymorphisms rs769217 showed a weak association with type 1 diabetes. Regarding rs1001179 polymorphism patients with TT genotype have a risk for lower life expectancy.  In acatalasemics the frequency of diabetes mellitus is higher (P˂0.001) than in the Hungarian population. 11 of 12 known Hungarian acatalasemia mutations are found in diabetic patients. Acatalasemia may be associated with a higher risk for diabetes mellitus especially for its type 2 form. Acatalasemia mutations could explain the decreased (˂50%) blood catalase activities only in 17.4% of the cases.  Conclusions: Blood catalase activity is decreased in type 2 and gestional diabetes. Patients with inherited catalase deficiency and known acatalasemia mutation are at higher risk of diabetes mellitus. The lifelong effect of oxidative damage on the oxidant sensitive, insulin producing pancreatic beta-cells could contribute to the manifestation of diabetes mellitus especially to type 2 form. Acatalasemia mutations could explain the reason for the catalase decrease while for the other (82.6 %) cases it remains unsolved. The decreased blood catalase activity in type 2 and gestational diabetes rather due to regulatory mechanisms than to the catalase gene mutations.